Functional Mechanisms of Health Behavior Change Techniques: A Conceptual Review - Michaelsen, Maren M.; Esch, Tobias (Frontiers in Psychology, 2022)
Background: Health behavior change is among the top recommendations for improving health of patients with lifestyle-related chronic diseases. An array of behavior change techniques (BCTs) have been developed to support behavior change initiation and maintenance. These BCTs often show limited success when they are not informed by theory, leading to a mismatch between the intention of the BCT and patients’ needs or expectations. Previous studies have identified a number of resources (domains) which patients may require to initiate and maintain health behavior change. Indeed, not yet well established is how BCTs address these resources, i.e., the functional mechanisms of BCTs. Purpose: Provide a theoretical framework of the functional mechanisms of BCTs for developing and implementing successful interventions for health behavior change. Methods: Conceptual review, including literature analysis and synthesis as well as conceptualization of a new model based on the synthesis. Results: Through the integration of dual-process models as well as reward and motivation proceeding, i.e., affective, emotional or intuitive neurobiological cues, into the rational framework of rather linear cognitive or task-related decision progress, we categorize previously identified resources into three distinct sets: external, internal reflective and internal affective resources. Based on this triad, we classify BCTs according to their functional mechanisms into facilitating (= providing external resources), boosting (= strengthening internal reflective resources) and nudging (= activating internal affective resources). Consequently, we present a simplified behavior change resource model (BCRM) that is centered on patients’ resources. Conclusion: The model can be applied to develop health behavior change interventions, which promote engagement and empowerment. Future studies should aim at testing the applicability and practicality of the BCRM.